2008
DOI: 10.4196/kjpp.2008.12.5.281
|View full text |Cite
|
Sign up to set email alerts
|

Tyrphostin ErbB2 Inhibitors AG825 and AG879 Have Non-specific Suppressive Effects on gp130/ STAT3 Signaling

Abstract: Although the interaction between gp130 and the ErbB family has frequently been shown in cancer cells, the mechanism of this interaction remains unclear and controversial. In the present study, we found that specific tyrphostin inhibitors of ErbB2 (AG825 and AG879), but not ErbB1 inhibitor (AG1478), suppressed IL-6-induced tyrosine phosphorylation of STAT3 in schwannoma cells. However, biochemical evidence for transactivation of ErbB2 by IL-6 was not observed. Additionally, the inhibition of ErbB2 expression, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…MIN-6 cells were stimulated with BTC (0.5 nM) for 24 h in the presence of 4 nM of AG1478 or AG825. AG1478 is known as a potent and selective inhibitor of ErbB-1 (IC 50 = 3 nM), but does not inhibit ErbB-2 (IC 50 >100 µM) [23] , and AG825 is a specific inhibitor of ErbB-2 [24] . Treatment of the cells with either inhibitor significantly suppressed BTC-induced DNA synthesis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MIN-6 cells were stimulated with BTC (0.5 nM) for 24 h in the presence of 4 nM of AG1478 or AG825. AG1478 is known as a potent and selective inhibitor of ErbB-1 (IC 50 = 3 nM), but does not inhibit ErbB-2 (IC 50 >100 µM) [23] , and AG825 is a specific inhibitor of ErbB-2 [24] . Treatment of the cells with either inhibitor significantly suppressed BTC-induced DNA synthesis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To predict the agent that might reverse the DEGs profiles, the DEGs were submitted to CMAP tool [24] for analysis. Consequently, a list of agents was screened out, of which Tyrphostin AG-825, a specific tyrphostin inhibitor of ErbB2, [25,26] had the highest negative enrichment score. Evidence showed that AG-825 have tumor suppressive function for multiple ErbB2-overexpressing cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence showed that AG-825 have tumor suppressive function for multiple ErbB2-overexpressing cancer cells. [25,26] Meanwhile, Bo-Jeng Wang et al [27] found that ErbB2 may play a critical role in the pathogenesis of AD. The expression of ErbB2 is considered dormant during adulthood but reactivated during the pathogenesis of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Tyrphostin AG879 has long been widely used as a protein tyrosine kinase inhibitor and is known to have beneficial anti‐tumour properties, which include inhibition of NGF‐induced PLC‐γ 1 phosphorylation and PI3K activation (Ohmichi et al ., ; Rende et al ., 2000; 2006), inhibition of ErbB2 receptors and the VEGF receptor 2 (FLK‐1) (He et al ., 2001; 2004; Zhou and Brattain, ; Lee et al ., ) and indirect inhibition of the MAPK cascade (Gil et al ., ; Larsson, ). Although AG879 potently inhibits, with an IC 50 of 1 μM, the expression of human epidermal growth factor receptor 2/ErbB2 receptors, the compound starts to cause apoptosis or reduce the proliferation of cells at concentrations more than 5∼20 μM in TrkA‐highly expressed tumour cell lines (Rende et al ., ).…”
Section: Discussionmentioning
confidence: 99%